Technique for Diagnostic Radiology of clavicular fractures - Quesada, Fortunato (1926)
When the method commonly adopted to make a diagnostic radiology in cases of fracture of the clavicle, consisting of an X-ray shots in the front direction, focusing the rays at the midpoint of the clavicle or printing two plates according to the technique is still stereoscopic flaws that can be seen are remarkable.